2013
DOI: 10.1371/journal.pone.0069179
|View full text |Cite
|
Sign up to set email alerts
|

Against All Odds: Genocidal Trauma Is Associated with Longer Life-Expectancy of the Survivors

Abstract: Does surviving genocidal experiences, like the Holocaust, lead to shorter life-expectancy? Such an effect is conceivable given that most survivors not only suffered psychosocial trauma but also malnutrition, restriction in hygienic and sanitary facilities, and lack of preventive medical and health services, with potentially damaging effects for later health and life-expectancy. We explored whether genocidal survivors have a higher risk to die younger than comparisons without such background. This is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 16 publications
6
30
1
1
Order By: Relevance
“…In contrast to our results, a study of young immigrants from Poland to the prestate of Israel found that those potentially exposed to the Holocaust (immigrated between 1945 and 1950) had a slightly longer life expectancy than those who immigrated before 1939. 12 Our results are supported by a study of Norwegian survivors of German concentration camps, which found minor increases in mortality and cancer-specific mortality over that of the Norwegian population. 13 Overall mortality was increased particularly in the early calendar periods, lung cancer being the main reason for the increase.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast to our results, a study of young immigrants from Poland to the prestate of Israel found that those potentially exposed to the Holocaust (immigrated between 1945 and 1950) had a slightly longer life expectancy than those who immigrated before 1939. 12 Our results are supported by a study of Norwegian survivors of German concentration camps, which found minor increases in mortality and cancer-specific mortality over that of the Norwegian population. 13 Overall mortality was increased particularly in the early calendar periods, lung cancer being the main reason for the increase.…”
Section: Discussionsupporting
confidence: 81%
“…The hypothesis that selective mortality, possibly reflecting trait and/or learned resilience, left Holocaust survivors at a reduced risk of dementia was not supported (Barel et al, 2010;Sagi-Schwartz et al, 2013;Solomon & Prager, 1992). Selective mortality likely occurred as some vulnerable people exposed to the adverse conditions of the Holocaust may have remained alive, such as those who were hidden (e.g., in convents and/or by non-Jewish families).…”
Section: Discussionmentioning
confidence: 99%
“…Protracted and severe anti‐Semitic persecutions of the European genocide (Lemkin, ) known as the Holocaust (Bauer, ) generated maximum adversity among survivors (Levav, ). Observational studies have indicated that survivors are at a higher risk of cancer (Keinan‐Boker, Vin‐Raviv, Liphshitz, Linn, & Barchana, ) and schizophrenia (Levine, Levav, Goldberg, et al., ) as well as some other psychiatric disorders (Barel, van IJzendoorn, Sagi‐Schwartz, & Bakermans‐Kranenburg, ; Sharon, Levav, Brodsky, Shemesh, & Kohn, ) yet have a longer life expectancy (Sagi‐Schwartz, Bakermans‐Kranenburg, Linn, & van Ijzendoorn, ) and lower risk of suicide (Levine, Levav, Yoffe, Becher, & Pugachova, ) than comparison groups. Such diverse results of the traumatic experiences of Holocaust exposure may be explained by competing hypotheses of survivor resilience versus vulnerability, as highlighted by a systematic review and meta‐analysis (Barel et al., ), which did not cover dementia as no studies in which it was examined had been published at that time.…”
mentioning
confidence: 99%
“…Third, Holocaust survivors may consist of highly resilient individuals who were able to survive both prolonged physical and psychological trauma. It was previously shown that Holocaust survivors have higher lifeexpectancy as compared to those who did not go through the same experience, potentially due to selection during the Holocaust (Sagi-Schwartz et al, 2013), and a genetic basis to this resilience was proposed Konečná et al, 2019). Genetic factors contributing to this resilience may contribute to recovery of elevated mtDNA copy number and maintaining telomere length (Konečná et al, 2019), though it is unclear if the same factors confer protection against PTSD and other disorders.…”
Section: Discussionmentioning
confidence: 99%